Reviews (Reviews in religion and theology, 2000)
Books reviewed Donald Wiebe, The Politics of Religious Studies: The Continuing Conflict with Theology in the Academy Timothy Fitzgerald, The Ideology of Religious Studies John Witte Jr and Richard C. Martin (eds), Sharing the Book: Religious Perspectives on the Rights and Wrongs of Proselytism Paul J. Griffiths, Religious Reading: The Place of Reading in the Practice of Religion Shaye J. D. Cohen, The Beginnings of Jewishness. Boundaries, Varieties, Uncertainties José Faur, Homo Mysticus: A Guide to Maimonides's Guide for the Perplexed Kenneth Cragg, The Weight in the Word – Prophethood: Biblical and Qur'anic Kenneth Cragg, Readings in the Qur'an James Howard-Johnston and Paul Antony Hayward (eds), The Cult of Saints in Late Antiquity and the Middle Ages: Essays on the Contribution of Peter Brown John McManners, Church and Society in Eighteenth-Century France, Volume 1 The Clerical Establishment and its Social Ramifications, Volume 2 The Religion of the People and the Politics of Religion Nigel Scotland,‘Good and Proper Men ’: Lord Palmerston and the Bench of Bishops David N. Livingstone, D. G. Hart, Mark A. Noll (eds), Evangelicals and Science in Historical Perspective Alistair Kee, Nietzsche against the Crucified Wallace W. Zane, Journeys to the Spiritual Lands: The Natural History of a West Indian Religion William P. Anderson and Richard L. Diesslin, A Journey through Christian Theology: With Texts from the First to the Twenty-first Century David Coffey, Deus Trinitas: The Doctrine of the Triune God Reinhard Hutter, Suffering Divine Things: Theology as Church Practice John W. de Gruchy (ed.), The Cambridge Companion to Dietrich Bonhoeffer Geffrey B. Kelly and C. John Weborg (eds), Reflections on Bonhoeffer: Essays in Honour of F. Burton Nelson George Hunsinger, Disruptive Grace: Studies in the Theology of Karl Barth Richard Bauckham (ed.), God will be All in All: The Eschatology of Jürgen Moltmann Paul Avis, God and the Creative Imagination Nicholas Sagovsky, Ecumenism, Christian Origins and the Practice of Communion Paul Helm, Faith with Reason Alvin Plantinga, Warranted Christian Belief Lisa Barnes Lampman and Michelle D. Shattuck (eds), God and the Victim: Theological Reflections on Evil, Victimization, Justice, and Forgiveness Gregory Baum (ed.), The Twentieth Century: A Theological Overview Frank Graziano, The Millennial New World Jennifer E. Porter and Darcee L. McLaren (eds),Star Trek and Sacred Ground: Explorations of Star Trek, Religion, and American Culture Eugene F. Rogers Jr, Sexuality and the Christian Body: Their Way Back into the Triune God Liam Gearon (ed.), English Literature, Theology and the Curriculum Robert Detweiler and David Jasper (eds), Religion and Literature: A Reader G. R. Evans and Martyn Percy (eds), Managing the Church? Order and Organization in a Secular Age